Precipitation and not cover crop composition influenced corn economic optimal N rate and yield. (25th January 2023) - Bielenberg, Hunter; Clark, Jason D.; Sanyal, Debankur; Wolthuizen, John; Karki, David; Rahal, Amin; Bly, Anthony
Abstract: The effects of single species cover crops on corn ( Zea mays L.) N requirement and grain yield are well studied throughout the U.S. Midwest. However, comparing cover crop mixes that include different compositions of grass and broadleaf species is limited. Fourteen corn N response experiments were conducted in South Dakota from 2018 to 2021. Fall cover crops planted after small grain harvest were mixtures of dominantly grasses, broadleaves, a 50/50 grass/broadleaf mixture, and a no cover crop control. Compared to the control, including a cover crop led to no differences in economic optimal N rate (EONR) and yield at zero N (0N) and yield at EONR 44%, 62%, and 83% of the time, respectively. As spring cover crop/residue biomass and its C and N content increased, corn yield at EONR decreased and EONR increased when including cover crops ( R 2  = 0.36–0.56). Including cover crops reduced EONR and resulted in a similar yield when precipitation increased above 850 mm. When differences occurred with economic return from N, including a cover crop reduced economic return in 3 site‐years (mean decrease of US$358 ha −1 ) and in only 1 site‐year did including a grass cover crop increase economic return from N (+US$335 ha −1 ). Thus, in the first year of growing cover crops (i.e., grasses, broadleaves, or a grass/broadleaf mix) before corn, growers can normally expect some differences in EONR. However, with the appropriate rate of N, yield at EONR is maintained and any economic differences from N normally minimized. Core Ideas: Three cover crop mixtures (grass, broadleaf, and 50/50 grass/broadleaf) and a no cover crop control were compared. When EONR differences occurred, including cover crops more often increased EONR (39%) opposed to decreasing it (17%). Including cover crops did not affect grain yield at EONR 83% of the time and reduced it 17% of the time. Reduced EONR and similar yield with cover crops correlated with precipitation greater than 850 mm. Greater EONR and reduced yield with cover crops correlated with greater cover crop biomass and its C and N content.